The Effect of Low Birthweight on the Incidence of Neonatal Jaundice in Sidoarjo - Ndaru Puspita (Universitas Airlangga, 2018)
Background : The incidence of neonatal jaundice on low birth weight babies (BBLR) are mostly lead to mortality. A preliminary survey in the neonatal room of the public hospital (RSUD) Sidoarjo in January to December 2013 showed that there were 391 (12%) babies born with low birth weight from 3,210 natalities with 375 (9%) neonatal jaundice recorded from 3878 babies. Purpose: This study aimed to investigate the influence of low birth weight on the incidence of neonatal jaundice in RSUD Sidoarjo. Methods: The study design was a cross-sectional study with a total of 190 babies included as the study population. However, there were only 129 babies selected as respondents determined from solving formula with randomized sampling method. There were two variables measured in this study, namely low birth weight, and neonatal jaundice incidents. The secondary data were obtained from patients’ medical records and were analyzed through a chi-square test to investigate the correlation between the two variables. Results: Results showed that the percentage of babies born with low birth weight was 21.71% and the neonatal jaundice was 29.46%. The number of babies suffered from neonatal jaundice with low birth weight was 17.80% with p=0.01. Conclusion: By all means, the low birth weight has a contribution in the incidence of neonatal jaundice in RSUD Sidoarjo.